The Influence of Consumer Taste, Brand Awareness, and Product Differentiation on Purchasing Decisions for Sarimi Instant Noodle Products with Income Level as an Intervening Variable: The Influence of Consumer Taste, Brand Awareness, and Product Differentiation on Purchasing Decisions for Sarimi Instant Noodle Products with Income Level as an Intervening Variable - Rahmawati, Kania; Indriasari, Ika; Ervina Indiworo, Rr Hawik (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
The purpose of this study is to examine the relationship between income level, customer taste, brand awareness, and product differentiation as they pertain to the purchase of Sarimi instant noodle products. To further optimize customer purchase choices for Sarimi instant noodle products, this study may be used as input into the preparation and determination of relevant marketing management strategies. Sarimi instant noodle product buyers in Pati Regency make up the study’s population. How the research’s sample was chosen A non-probability w sampling approach is used in this. One hundred participants will be polled as part of this study’s Purposive Sampling strategy, which is based on predetermined criteria and the moe formula. This research employed SEM analysis in conjunction with SmartPLS version 3 for data analysis. The research and discussion findings partly reveal customer preferences There are several factors that influence purchasing decisions. One of these is income levels. Consumer tastes have an influence on purchasing decisions, which is mediated by income level. Brand awareness also influences purchasing decisions, through income level. When it comes to Sarimi Instant Noodle Products, product differentiation influences purchasing decisions by partically by Income Level .